Determinação Eletroanalítica de Nitratos, Nitritos e Nitrosaminas - Almeida, Isadora Ponciano (2021)
The animal origin products consumption, such as meat and meat products, has in- creased globally, mainly due to the increase in family income. As a consequence, the demand for high quality and safe meat products has become increasingly greater. In this way, the food additives use ensure these products desirable sensory properties, such as color, odor, taste and texture, besides that food quality and safety. Among these additives, sodium nitrate and nitrite are the most largely used substances, since that act in the curing processes of meat products. However, if used in inadequate con- centrations, these compounds can result in the production of N-nitrous compounds, such as N-nitrosamines, which are volatile amines that may be related to the emer- gence of public health problems, including the development of some types of cancer. Therefore, these compounds must be monitored so that the amount added to food is adequate, ensuring that only the compounds allowed by specific legislation are used during the preparation of meat products and other types of processed foods. Thus, in this work, a literature review was carried out involving the scientific productions pub- lished between the year 2010 to 2021 and related to the development and application of analytical methodologies for the identification and quantification of nitrates, nitrites and nitrosamines in natural waters and industrialized foods. For this, the application of chromatographic, spectroscopic and electroanalytical techniques was considered, with emphasis on the application of electroanalytical techniques. The evaluation of the pub- lications was carried out considering the searches in the scientific databases Science Direct, Scopus and Web of Science, using as keywords the terms nitrates, nitrites, or nitrosamines together with the terms chromatographic techniques, or spectroscopic techniques or electroanalytical techniques. Thus, 268 articles were found involving the use of electroanalytical techniques, 169 articles involving the application of spectro- scopic techniques and 134 articles using the application of chromatographic tech- niques for detection of nitrates, nitrites and nitrosamines in samples of food, beverages and natural waters.